Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1128/jb.187.24.8350-8360.2005
|View full text |Cite
|
Sign up to set email alerts
|

luxS-Dependent Gene Regulation inEscherichia coliK-12 Revealed by Genomic Expression Profiling

Abstract: The bacterial quorum-sensing autoinducer 2 (AI-2) has received intense interest because the gene for its synthase, luxS, is common among a large number of bacterial species. We have identified luxS-controlled genes in Escherichia coli under two different growth conditions using DNA microarrays. Twenty-three genes were affected by luxS deletion in the presence of glucose, and 63 genes were influenced by luxS deletion in the absence of glucose. Minimal overlap among these gene sets suggests the role of luxS is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
151
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(161 citation statements)
references
References 55 publications
6
151
0
3
Order By: Relevance
“…Therefore, YncC binding of the promoter regions of the two most-induced genes in both glass wool and agar biofilm cells (ybiM and sfsA, Table 2), the two most-induced genes in glass wool biofilm cells (ybeL and uspF, Table 2), as well as with the one of the most repressed genes in glass wool biofilm cells (yebT, Table 3) was investigated using gel shift experiments. We were especially interested in ybiM and yebT since not only were they differentially expressed on yncC mutation but also both of them are regulated by AI-2 (DeLisa et al, 2001b;Wang et al, 2005). It was found that YncC binds to the promoter region of the ybiM gene (Figure 3a), but YncC did not bind under these conditions to the promoter regions of ybeL, sfsA, uspF and yebT (Figure 3b and data not shown).…”
Section: Yncc Represses Ybimmentioning
confidence: 99%
“…Therefore, YncC binding of the promoter regions of the two most-induced genes in both glass wool and agar biofilm cells (ybiM and sfsA, Table 2), the two most-induced genes in glass wool biofilm cells (ybeL and uspF, Table 2), as well as with the one of the most repressed genes in glass wool biofilm cells (yebT, Table 3) was investigated using gel shift experiments. We were especially interested in ybiM and yebT since not only were they differentially expressed on yncC mutation but also both of them are regulated by AI-2 (DeLisa et al, 2001b;Wang et al, 2005). It was found that YncC binds to the promoter region of the ybiM gene (Figure 3a), but YncC did not bind under these conditions to the promoter regions of ybeL, sfsA, uspF and yebT (Figure 3b and data not shown).…”
Section: Yncc Represses Ybimmentioning
confidence: 99%
“…LsrR has been revealed to be able to repress transcription from the lsrA and lsrR promoters, with deletion of lsrR resulting in maximal transcription of the lsr operon and the lsrR gene in S. typhimurium and E. coli [26,31]. Since LsrR contains a predicted HTH DNA-binding domain, it has been suggested to repress the transcription of the lsr operon and itself by directly binding to their promoters.…”
Section: Lsrr Binds To Lsra and Lsrr Promotersmentioning
confidence: 99%
“…The "basic" K-12 proteome comprises 3897 proteins (supplemental Table S4A). The transcripts encoding 3849 of these polypeptides (42)(43)(44)(45) as well as 3178 of these polypeptides have been detected in cells grown in LB broth (48,49).…”
Section: Resultsmentioning
confidence: 99%
“…transcribed at mRNA level) were considered to be all genes that have transcripts identified as "present" at either of four microarray datasets (42)(43)(44)(45)(46) or quantified in single cell analyses (44).…”
Section: Methodsmentioning
confidence: 99%